A training impact evaluation of the higher education programmes: a case study of the Elsenburg Agricultural Training Institute - Hendrikse, Shawn Basil (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPA)--Stellenbosch University, 2017.